From Crypto-Muslim to Muslim Polemicist: The Self-Writing of Aḥmad ibn Qāsim al-Ḥajarī - Gibson, Paige (AUC Knowledge Fountain, 2024)
This thesis examines the self-writing of the Morisco writer Aḥmad ibn Qāsim al-Ḥajarī (b. 1569–1570) who fled his homeland in Spain for the Maghreb where he could live safely as a Muslim. While it may seem that the Moriscos were one static, monocultural group, studying them as individuals reveals the group’s diversity and complexity. Al-Ḥajarī is an excellent example of one Morisco writer who identifies more with the greater Muslim community than with the Iberian Moriscos. His most well-known work, Kitāb Nāṣir al-dīn, combines Arabic literary genres in order to create this self-portrait. Other Moriscos fought for their right to stay on the peninsula, whereas Kitāb Nāṣir al-dīn is the story of how and why al-Ḥajarī willingly left Iberia. Through analysis of both the content and the structure of this text, this thesis shows how Kitāb Nāṣir al-dīn can be considered the autobiography of al-Ḥajarī despite autobiography being considered a Western genre that only surfaced in modern times. Further, this thesis brings to light an individual who shifted between cultures during a time where cultures appear to have been divided by religion, culture and language.